Morbidities, Complications and Outcomes at Discharge in Newborns Admitted with Respiratory Distress at a Tertiary Care Hospital ofNepal: A Descriptive Cross-Sectional Study - Shah, Prakash Man; Bhatta, Nisha Keshary; K.C, Subash; Sah, Sukrita; K.C, Sri Ram; Karki, Rajani; Pokharel, Samikshya (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Neonatal respiratory disorders are among the leading causes of admissions to neonatal intensive care units due to respiratory distress in the early neonatal period. However, studies on their spectrum and outcomes among Nepalese neonates are limited. This study aimed to find out the proportion and types of respiratory disorders among admitted newborns, along with associated complications and outcomes.Methods: This descriptive cross-sectional study was conducted in the Neonatology Unit of a tertiary care hospital from July 1, 2023 to June 30, 2024, among all inborn neonates meeting the inclusion criteria. Convenience sampling was applied, and the sample size taken was 150. Ethical approval was obtained from the Institutional Review Committee (Ref no 241/080/081-IRC). Data were entered in Microsoft Excel 2007 and analyzed using Statistical Package for the Social Sciences version 11.5.Results: Among 150 newborns, the most prevalent morbidity was Transient Tachypnoea of Newborn 56 (37.30%), followed by Meconium Aspiration Syndrome 46 (30.70%). Similarly, 27 (18%) had complications, and 123 (82%) had no complications. Likewise, 134 (89.30%) babies recovered and were discharged, and 7 (4.70%) died during the course of treatment.Conclusions: This study concluded that the most common morbidity was Transient Tachypnea of the Newborn, followed by Meconium Aspiration Syndrome. This study emphasizes early identification of different types of respiratory disorders and common complications among neonates with respiratory distress which will help in early recognition and treatment thereby minimizing complications and mortality.